The use of distance learning through whatsapp and google meeting to identify differences in biology learning outcomes - Permana, Fendy Hardian; Sukma, Ellisa; Wahyono, Poncojari (Universitas Negeri Jakarta, 2021)
The COVID-19 pandemic has turned face-to-face learning into distance learning using online media. Educational institutions strive to provide a system to meet students' needs in conducting distance learning using online media. Educational institutions also try to familiarize teachers and students with using online media in the learning process. Educators and students can utilize distance learning media in Whatsapp groups and google meetings to carry out the learning process. This study aims to determine whether there are differences in student biology learning outcomes between the experimental class I learning using WhatsApp group and the practical class II learning using google meetings. This type of research is a quasi-experimental design with a posttest-only control design. The study population was all class X MIPA (mathematics and science) Public Senior High School 02 Batu (There are five classes). The sampling technique used purposive sampling. The experimental class I was class X MIPA 4 with 28 students and the practical class II was class X MIPA 5 with 28 students. Descriptive and inferential statistical data analysis techniques using Ms. Excell and the Independent Sample T-Test (SPSS Statistics 17.0). This study indicates that there is a difference in the average learning outcomes of students between experimental class I (74.75) who carry out learning using WhatsApp group and experimental class II (64.75) who carry out learning using google meetings. In conclusion, learning using the WhatsApp group is better.